2017
DOI: 10.4103/jcvjs.jcvjs_61_17
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative complications in patients treated with posterior cervical fusion and bilateral cages

Abstract: Context:Posterior cervical cages have recently become available as an alternative to lateral mass fixation in patients undergoing cervical spine surgery.Aims:The purpose of this study was to quantify the perioperative complications associated with cervical decompression and fusion in patients treated with a posterior cervical fusion (PCF) and bilateral cages.Settings and Design:A retrospective, multicenter review of prospectively collected data was performed at 11 US centers.Subjects and Methods:The charts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…13 The mean LOS across our entire systematic review ranged from 26 to 33.6 hours [13][14][15]17 and suggests a significant improvement on traditional posterior cervical fusion, which ranges from 4.0 to 7.3 days. [21][22][23][24][25][26][27][28] Additionally, the mean EBL in this review ranged from 32.83 to 87.8 cm 3 for the tissue-sparing, posterior interfacet fusion, [13][14][15]17 which compares favorably to open posterior cervical fusions (range, 225-480 cm 3 ). [21][22][23][24][25][26][27][28]…”
Section: Intraoperative Outcomesmentioning
confidence: 94%
See 3 more Smart Citations
“…13 The mean LOS across our entire systematic review ranged from 26 to 33.6 hours [13][14][15]17 and suggests a significant improvement on traditional posterior cervical fusion, which ranges from 4.0 to 7.3 days. [21][22][23][24][25][26][27][28] Additionally, the mean EBL in this review ranged from 32.83 to 87.8 cm 3 for the tissue-sparing, posterior interfacet fusion, [13][14][15]17 which compares favorably to open posterior cervical fusions (range, 225-480 cm 3 ). [21][22][23][24][25][26][27][28]…”
Section: Intraoperative Outcomesmentioning
confidence: 94%
“…After systematic review, a total of seven studies met inclusion criteria (Figure 1). 8,[12][13][14][15][16][17] All studies were classified as either retrospective cohort or prospective cohort. There were no studies with a control or comparison group.…”
Section: Included Studies and Quality Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Siemionow et. al investigated complications of 89 patients including primary PCC, PCC combined with ACDF and revision of pseudoarthrosis after ACDF with PCC with a mean 7-month follow-up [31]. The overall complication rate related to PCC surgery was 3,4%, which the authors reported was favorable when compared to anterior only approaches for single level cervical radiculopathy.…”
Section: Clinical and Radiological Outcomesmentioning
confidence: 99%